Multi-objective Optimization of Heterogeneous Liner Fleet Deployment with Shipping Downturn Considerations - Shihao Gong, Zhangchi Sun, Jiabao Zhao (Forest Chemicals Review, 2022)
This paper considers the optimization problem of fleet deployment during the shipping downturn for liner shipping companies. In the operation of the liner shipping companies, there is a rising trend to deploy a heterogenous fleet on certain route. Especially when the shipping market is depressed, the combination of ships with different carrying capacities (i.e., heterogeneous fleets) can reduce the waste of carrying capacity. The excessive transportation capacity will increase the capital cost and the maintenance cost. Consequently, the reduction of the capacity loss and the minimization of the operation cost of the liner ships are both vital for the liner shipping companies. The problem is formulated into a multi-objective optimization problem. And then an improved non-dominated sorting genetic algorithm-II (NSGA-II) is used to solve the problem. A case study is provided to illustrate the application of the model.